Effect of Urmia Lake's drying on groundwater corrosion and scaling potential in the northwest of Iran (Case study: Spring and summer, 2015). Issue 4 (10th August 2018) - Zazouli, Mohammad Ali; Kalankesh, Laleh R.; Rodríguez‐Couto, Susana; Keshavarz, Ali
Abstract: The most common problems in water distribution systems are corrosion and scaling, which cause both economic and customer health problems. The aim of the present study is to report the relationship between Urmia Lake's drying and the corrosion and scaling potential of groundwater used as drinking water during the spring and summer of 2015. Groundwater samples were collected from all of the catchments of the Urmia Lake basin, and the characteristics of the water were used to determine the corrosive and scaling indices using the Langelier Saturation Index and the Ryznar Stability Index. The results showed that the total dissolved solids measurement of the samples collected from the islands of Urmia Lake was higher than the maximum value of the standard level. In addition, the hardness in 36% of the zones was higher than that of the maximum suggested level. The concentration of calcium was lower than that of the standard, but the rest of the parameters were in the standard level range. Also, the results showed that the water of the Urmia Lake basin tends to be very scaling and corrosive. In order to control the corrosion and scaling caused by groundwater drawn from the catchments around Urmia Lake, measures should be taken to prevent Urmia Lake's drying and to manage the groundwater around this area. It is also suggested that a laboratory study regarding the condition of the distribution system be carried out to adjust the effective parameters, such as the pH.